JTLU special issue editorial: Bicycling in changing urban regions - Krizek, Kevin J.; Sharmeen, Fariya; Martens, Karel (Journal of Transport and Land Use, 2018)
As communities around the globe contemplate the future of their transport portfolio, bicycling’s role has increasingly cropped up as a key discussion point. Up until a few years ago, bicycling’s value was largely fueled by a loyal advocacy base. Its potential was littered with unsupported claims and bicycling struggled to obtain legitimate status, even as, or precisely because of its status as a ’fringe mode.’ This context has recently changed. Concomitant with—or perhaps prompted by—a rise in (public and policy attention for) bicycling, there has been a rise in research specifically on bicycling. In just a few years, bicycling’s stock has risen to be a mode that is commanding attention in cities of all sizes. Furthermore, its role and value are informed by a burgeoning evidence base, increasingly in the form of peer-reviewed work. This evidence base allows, among other things, a more reflective appreciation for bicycling’s position in transport systems and for bicycling to be better understood in different geographical contexts.